Geometric Feature Extraction of Batik Image Using Cardinal Spline Curve Representation - Aris Fanani; Anny Yuniarti; Nanik Suciati (Universitas Ahmad Dahlan, 2014)
Batik is an Indonesian national heritage which has been recognized as a world cultural heritage (world heritage). Batik is widely used as clothing material. The advancement of technology allowed the material optimization in clothing design. Geometrical information of batik image is required in a modul for optimizing clothing design with batik as raw material. Geometric feature extraction of batik image is used to help computer to recognize batik's pattern or motif. This research proposes a method for geometric feature extraction of batik image by using cardinal spline curve representation. The method for geometric feature extraction is divided into 2 processes, i.e., feature extraction for Klowongan and feature extraction for Isen-Isen. Klowongan represents pattern of batik image, whereas Isen-Isen is content patterns of Klowongan. Feature extraction of Klowongan is performed by deleting collinear points from object boundaries until the dominant points are obtained. The dominant points are then used as control points. Feature extraction of Isen-Isen is performed by saving coordinate of every connected components which are also used as control points. Geometry feature of batik image is represented as a set of control points of klowongan and isen-isen. Batik image can be reconstructed by drawing cardinal spline curve using a set of control points in the geometric representation. The experiment shows that the reconstructed images is visually similar with the original batik image.